Survei Tingkat Kreativitas Guru Penjasorkes dalam Keterbatasan Sarana dan Prasarana dalam Proses Pembelajaran Penjasorkes di SD 3T se-Kecamatan Cenrana Kabupaten Bone - Agung, Agung Purnomo; Khalid Rijaluddin; Maria Herlinda Dos Santos (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to determine a survey of the level of creativity of physical education teachers within the limited facilities and infrastructure in the physical education learning process at SD3T in Cenrana District, Bone Regency. This type of research is quantitative descriptive. The results of the research show that how high the level of creativity of Physical Education teachers is within the limited facilities and infrastructure in the Physical Education learning process at SD3T SE-Cenrana District, Bone Regency, for the